A Comparison of the Effects of Citicoline and Piracetam on Hypoxic-ischemic Brain Damage in Neonatal Rabbits - Ebrahimi, Sedigheh; Ashkani-Esfahani, Soheil; Ebrahimi, Alireza (Iranian Journal of Child Neurology, 2022)
Abstract Objectives Perinatal hypoxic-ischemic brain injuries have been a major cause of mortality and neurodevelopmental morbidities in newborns. Citicoline and Piracetam have been used as nootropic agents in a number of studies. In this investigation, we aimed to determine the effects of these agents solely and in combination in hypoxicischemic brain damage in rabbit neonates. Materials & Methods Hypoxic-ischemic brain damage was induced by the occlusion of both uterine arteries of dams for eight minutes. The subjects were randomly divided into five groups as follows (n=6 per group): control group without hypoxia (C1), control group with hypoxicischemic damage (C2), the third group (P) received Piracetam (100 mg/kg), the fourth group (T) administered with Citicoline (250 mg/ kg), and the fifth (PT) received both. The preventive effects of the two drugs on hypoxic-ischemic brain damage were microscopically investigated by the rates of damage to the hippocampus. Results Neuronal destruction rates in C1, C2, P, T, and PT were 4%, 45%, 37.5%, 12.5% (P=0.01 vs. C2), and 20% (P=0.03 vs. C2), respectively. The total means of hypoxic-ischemic damage, cell edema, neuronal degeneration, and eosinophilic degeneration were lower in the T group compared to C2 (P<0.05). Conclusion According to our results and previous findings, Citicoline as a treatment for hypoxic-ischemic brain injuries could be beneficial, and it has priority over neuroprotective agents like Piracetam. Moreover, the combination of Citicoline and Piracetam showed no superior effect in contrast with Citicoline alone. However, experimental studies on larger populations and clinical trials are highly suggested